Effects of nutritional manipulation on body composition in the developing marsupial, Macropus eugenii. (15th June 2016) - Hetz, Jennifer A.; Menzies, Brandon R.; Shaw, Geoffrey; Stefanidis, Aneta; Cowley, Michael A.; Renfree, Marilyn B.
Abstract: When 60-day-old tammar wallaby pouch young ( Macropus eugenii ) are fostered to mothers at 120 days of lactation, their growth, developmental rate and maturation of their GH/IGF axes are markedly accelerated. To determine the effect of fostering on energy intake, body composition and fat accretion, we first measured total body fat and lean mass in these young. Next, we mimicked the triglyceride oleic and palmitic acid composition of 120-day milk by supplementing 60 day young with these fatty acids and comparing their growth with that of growth accelerated young. There was no difference in the weight or growth axis maturation of supplemented young but there was significantly more body fat in these and in the growth-accelerated fostered young than in controls. We conclude that the accelerated growth and GH/IGF axis maturation observed previously in fostered young is most likely due to increased milk consumption and earlier access to specific nutrients. Graphical abstract: Highlights: Growth accelerated tammar foster young have more body fat than normal. Fatty acid supplements do not accelerate GH/IGF growth axis maturation or weight. Increased milk intake and early access to late stage nutrients accelerates growth.